1993
DOI: 10.1093/carcin/14.3.539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary retinoic acid on skin papilloma and carcinoma formation in female SENCAR mice

Abstract: Previously we have shown that dietary retinoids are essential for papilloma formation induced by either an initiation-promotion or a complete skin carcinogenesis protocol. The present study was conducted to further determine the effect of dietary retinoic acid (RA) on papilloma formation and the conversion of papillomas to carcinomas. Skin tumors were induced in 3 week old female SENCAR mice by an initiation-promotion protocol with one application of 20 micrograms of 7,12-dimethylbenz[a]anthracene (DMBA), foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…RA and its analogues (retinoids) are used in the therapy of dermatological 5,6 and neoplastic diseases, 7 although their clinical usefulness is limited by their proven teratogenic potential 8–10 . Retinoids have been shown to be effective in the prevention of skin cancer 7 in different animal models, following either topical application 11 or oral administration 12,13 . However, there appears to be nothing known about the in vivo long‐term effects on skin carcinogenesis after prenatal RA exposure in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA and its analogues (retinoids) are used in the therapy of dermatological 5,6 and neoplastic diseases, 7 although their clinical usefulness is limited by their proven teratogenic potential 8–10 . Retinoids have been shown to be effective in the prevention of skin cancer 7 in different animal models, following either topical application 11 or oral administration 12,13 . However, there appears to be nothing known about the in vivo long‐term effects on skin carcinogenesis after prenatal RA exposure in mice.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Retinoids have been shown to be effective in the prevention of skin cancer 7 in different animal models, following either topical application 11 or oral administration. 12,13 However, there appears to be nothing known about the in vivo long-term effects on skin carcinogenesis after prenatal RA exposure in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in mouse models as well as in vitro culture systems show that the proliferation of tumor cells is more sensitive to RA than of normal cells (Fountzilas, 1994). Dietary RA inhibits malignant conversion of skin papillomas to carcinomas induced by a two-stage carcinogenesis protocol in mice (De Luca et al, 1993). Long-term oral administration of 13-cis-RA reduced tumor formation in patients with Xeroderma pigmentosum (Kraemer et al, 1988).…”
Section: Ra and Cancermentioning
confidence: 99%
“…7) It has been reported that high doses of -carotene substantially reduced the malignant conversion of papillomae to carcinomas as well as retinoic acid. 8,9) Because both provitamin A carotenoids and retinoids are used as potential protective agents in tumor formation, the molecular mechanisms of the action of carotenoids is probably mediated at least in part by retinoic acid.Topical treatments of retinoic acid have been found to be beneficial to photodamaged skin. 10,11) Retinoic acid inhibits UV-caused loss of procollagen synthesis, 12) the induction of matrix metalloproteinases, 13) and the tortuosity of elastic fibers.…”
mentioning
confidence: 99%
“…7) It has been reported that high doses of -carotene substantially reduced the malignant conversion of papillomae to carcinomas as well as retinoic acid. 8,9) Because both provitamin A carotenoids and retinoids are used as potential protective agents in tumor formation, the molecular mechanisms of the action of carotenoids is probably mediated at least in part by retinoic acid.…”
mentioning
confidence: 99%